Variants in triggering receptor expressed on myeloid cells 2 are associated with both behavioral variant frontotemporal lobar degeneration and Alzheimer’s disease (2013)
ABSTRACT: Recent evidence suggests that rare genetic variants within the TREM2 gene are associated with increased risk of Alzheimer’s disease. TREM2 mutations are the genetic basis for a condition characterized by polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy (PLOSL) and an earlyonset dementia syndrome. TREM2 is important in the phagocytosis of apoptotic neuronal cells by microglia in the brain. Loss of function might lead to an impaired clearance and to accumulation of necrotic debris and subsequent neurodegeneration. In this study, we investigated a consanguineous family segregating autosomal recessive behavioral variant FTLD from Antioquia, Colombia. Exome sequencing identified a nonsense mutation in TREM2 (p.Trp198X) segregating with disease. Next, using a cohort of clinically characterized and neuropathologically verified sporadic AD cases and controls, we report replication of the AD risk association at rs75932628 within TREM2 and demonstrate that TREM2 is significantly overexpressed in the brain tissue from AD cases. These data suggest that a mutational burden in TREM2 may serve as a risk factor for neurodegenerative disease in general, and that potentially this class of TREM2 variant carriers with dementia should be considered as having a molecularly distinct form of neurodegenerative disease